Review on Needle Free Injection Technology - Narwade, P.S.; Bora, V.G.; Mhaske, P.S.; Sheikh, A.A.; Biyani, K.R. (Asian Journal of Pharmaceutical Research and Development, 2023)
Introduction: Needle-free injection technology (NFIT), its advantages, and the different devices and variants available. It highlights the potential of NFIT for painless and effective drug delivery and its use in mass vaccination campaigns. Methods: The primary factors that need to be considered to provide a stable, safe, and effective dose by NFIT. It also explains the classification of NFIT devices based on their working, type of load, mechanism of drug delivery, and site of delivery. Results: The additional benefit of NFIT technology, which is the ability to administer highly viscous medicated formulations that cannot be administered by conventional needle and syringe systems. It also highlights some of the commercially available variants of NFIT devices, such as Bioject®, ZetaJetTM, and Vitajet. Conclusion: The advantages and potential of NFIT for painless and effective drug delivery, particularly in mass vaccination campaigns and the developing world. It emphasizes the need for further research and development in this field to improve the stability, safety, and efficacy of NFIT devices.